Pengaruh Karakteristik Individu dan Lingkungan Kerja Terhadap Kinerja Pegawai Lapas Narkotika Banyuasin (Jurnal Manajemen dan Investasi (MANIVESTASI), 2021)
ABSTRACT       This study aims to determine the effect of individual characteristics and work environment on employee performance at the Banyuasin Narcotics Prison. The method used in this study is a quantitative method with the number of samples studied were 82 employees. The data analysis technique used in this research is multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and f test using the software program spss 23 for windows. From the results of the t test research shows that there is an effect of individual characteristics (X1) with a significant value of 0.000 0.05, meaning that partially there is no significant effect of the work environment on employee performance. From the results of the discussion of the F test simultaneously, a significant value of 0.000